Conservative Treatment of an Infected Aortic Graft with Antibiotic Irrigation - Akhtar, M.; Meecham, L.; Birkett, R.; Pherwani, A. D. P.; Fairhead, J. F. (International Journal of Angiology, 2016)
Conservative management of an aortic graft infection is defined as “the nonresectional treatment of an aortic graft that has an established infection.” Incidence of aortic graft infections is 0.5 to 5% and the estimated mortality rate from aortic graft infections ranges from 8 to 27%.We present the case of a 73-year-old male patient with an infected abdominal aortic graft following an emergency ruptured abdominal aortic aneurysm repair. Postemergency repair, he developed ischemic colitis with sigmoid colon perforation leading to fecal peritonitis and secondary sepsis. He developed a large infective collection within the aortic sac growing vancomycin-resistant enterococcus sensitive to linezolid. A percutaneous drain was placed in the aortic sac and this was irrigated with linezolid for a total of 28 days. The patient clinically improved. Overall, 7 months later, follow-up scan shows complete resolution of infection and the patient remains clinically stable.Conventional treatment of aortic graft infections involves an extra-anatomical bypass. Percutaneous drainage and antibiotic use may be used as bridging therapy for surgery or as definitive therapy when surgical treatment is impractical. Most aortic graft infections grow gram-positive cocci, the organisms form a biofilm which is protected from the external environment. Percutaneous drainage and antibiotic irrigation could possibly penetrate the biofilm and eradicate infection. Morris et al conducted a study on 10 patients having irrigation therapy and systemic antibiotic treatment and found a 1-year survival rate of 80%.In conclusion, conservative aortic graft treatment may be an effective alternative where surgical intervention is not suitable.
Keywords: abdominal aortic aneurysm; infected graft; infection; ischemia; percutaneous; repair; vascular access